1986
DOI: 10.2307/3430204
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Possible Health Effects of Aluminum

Abstract: Literature regarding the biochemistry of aluminum and eight similar ions is reviewed. Close and hitherto unknown similarities were found. A hypothetical model is presented for the metabolism, based on documented direct observations of Al3+ and analogies from other ions. Main characteristics are low intestinal absorption, rapid urinary excretion, and slow tissue uptake, mostly in skeleton and reticuloendothelial cells. Intracellular Al3+ is probably first confined in the lysosomes but then slowly accumulates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(55 citation statements)
references
References 26 publications
0
54
0
1
Order By: Relevance
“…The development of suitable biodegradable implant alloys is a multidisciplinary challenge, since freedom in alloy design must be confined to a range of alloying additions that are nontoxic in a medical sense. This rules out a large number of alloying elements common to commercial Mg alloys, including appreciable amounts of rare earth elements, some heavy metals, and to a large extent, aluminium 22, 23. A promising and biocompatible element is calcium (Ca), and while some limited studies to date have reported the use of Ca,24–26 a systematic and fundamental study of the role of Ca additions upon dissolution of Mg alloys in vitro is warranted and timely.…”
Section: Introductionmentioning
confidence: 99%
“…The development of suitable biodegradable implant alloys is a multidisciplinary challenge, since freedom in alloy design must be confined to a range of alloying additions that are nontoxic in a medical sense. This rules out a large number of alloying elements common to commercial Mg alloys, including appreciable amounts of rare earth elements, some heavy metals, and to a large extent, aluminium 22, 23. A promising and biocompatible element is calcium (Ca), and while some limited studies to date have reported the use of Ca,24–26 a systematic and fundamental study of the role of Ca additions upon dissolution of Mg alloys in vitro is warranted and timely.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that the element is involved in the development of both dementia (Graves et al 1990, Martin 1990, Wisniewski et al 1990) and osteomalacia (Drueke 1980, Costantini et al 1984, Zhu et al 1990) in patients undergoing dialysis, since it enters the blood stream directly from the water used in the process (Trapp 1983, Alfrey 1986). Although Al has been shown to be potentially toxic for the healthy population (Mayor et al 1977, Ganrot 1986, Flaten 1990), its bioavailabilit y is very low owing to both its low absorption by the gastrointestinal tract and its rapid urinary excretion (Alfrey 1989, Lote 1991. Problems can arise if the protection aOE orded by the gastrointestinal tract is circumvented.…”
Section: Introductionmentioning
confidence: 99%
“…Mg II seems to be one of the most affected cations, [9][10][11] since the two cations are of similar size, a factor that dominates over charge identity in metal competition. [9,12,13] Numerous examples of Al III inhibition of Mg II -dependent metalloenzymes have been reported. Hexokinase, adenylate cyclase, 3,5-cyclic nucleotide phosphodiesterase, acid and alkaline phosphatases, and acetylcholinesterase are well-documented examples [10] of Mg II substitution by Al III .…”
Section: Introductionmentioning
confidence: 99%